2017
DOI: 10.1007/978-3-319-47253-9_5
|View full text |Cite
|
Sign up to set email alerts
|

How Should Agent-Based Modelling Engage With Historical Processes?

Abstract: This paper consists of two main parts. After an introduction, the first part briefly considers the way that historical processes have been represented in ABM to date. This makes it possible to draw more general conclusions about the limitations of ABM in dealing with distinctively historical (as opposed to merely dynamic) processes. The second part of the paper presents a very simple ABM in which three such distinctively historical processes are analysed. These are the possible significance of unique individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Although they offer suggestions to get around the issue, the authors admit that “ABM appears to have blind spots about what makes history distinctive”. (Chattoe-Brown & Gabbriellini, 2017, p. 57) Chattoe-Brown and Gabriellini’s remark echoes an early prediction by Claudio Fogu, who felt that the advent of digital histories was moving historical imagination “towards a spatialization of historical experience, away from the temporal axis of narrative forms of historical consciousness”. (Fogu, 2009, p. 115) In his assessment, this process “detach[ed] the notion of history from its double reference to the past and to the real”.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Although they offer suggestions to get around the issue, the authors admit that “ABM appears to have blind spots about what makes history distinctive”. (Chattoe-Brown & Gabbriellini, 2017, p. 57) Chattoe-Brown and Gabriellini’s remark echoes an early prediction by Claudio Fogu, who felt that the advent of digital histories was moving historical imagination “towards a spatialization of historical experience, away from the temporal axis of narrative forms of historical consciousness”. (Fogu, 2009, p. 115) In his assessment, this process “detach[ed] the notion of history from its double reference to the past and to the real”.…”
Section: Introductionmentioning
confidence: 85%
“…Other authors have advanced a more worrisome concern: that simulations and history are fundamentally incompatible. Writing specifically about agent-based modeling (ABM), a genre of computer modeling focused on the interactions of autonomous agents with their environment, Edmund Chattoe-Brown and Simone Gabriellini observed that existing historical simulations often operate on “anthropological conception of history in which agents behave according to fixed social rules that are simply played out over time.”(Chattoe-Brown & Gabbriellini, 2017, p. 55) This runs counter historians’ understanding of history as a field in which change itself is the object of inquiry. Although they offer suggestions to get around the issue, the authors admit that “ABM appears to have blind spots about what makes history distinctive”.…”
Section: Introductionmentioning
confidence: 99%